Is there a Role for Epigenetic Enhancement of Immunomodulatory Approaches to Cancer Treatment? - Flower, Kirsty J.; Ghaem-Maghami, Sadaf; Brown, Robert (Current Cancer Drug Targets, 2018)
The efficacy of cancer immunotherapy relies on the ability of the host immune system to recognise the cancer as non-self and eliminate it from the body. Whilst this is an extremely fertile area of medical research, with positive clinical trials showing durable responses, attention must be paid to the subset of patients that do not respond to these treatments. Immune surveillance and immunoediting by the host could itself select for immune-evasive tumour cells during tumour development leading to immunotherapy resistance. One such mechanism of non-efficacy or resistance is the epigenetic silencing of a specific gene required in the immunotherapy response pathway. Epigenetics is the study of the control of expression patterns in a cell via mechanisms not involving a change in DNA sequence. All tumour types show aberrant epigenetic regulation of genes involved in all the hallmarks of cancer, including immunomodulation. Inhibition of key enzymes involved in maintenance of epigenetic states is another important area of research for new treatment strategies for cancer. Could epigenetic therapies be used to successfully enhance the action of immunomodulatory agents in cancer, and are they acting in the way we imagine? An understanding of the effects of epigenetic therapies on immunological pathways in both the tumour and host cells, especially the tumour microenvironment, will be essential to further develop such combination approaches.
Keywords: tumour microenvironment